A qualitative study on the mental and emotional well-being of first-year university students in Malaysia - Pauviya A/P Guna Segar; Azlina Mohd Kosnin; Lina Handayani (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study investigates the mental and emotional challenges faced by first-year university students in Malaysia to identify key factors influencing their adjustment to university life. Using a qualitative approach, semi-structured interviews were conducted with 15 first- and second-year students selected through purposive sampling. Conducting this research in Malaysia is essential, as limited studies have examined how local students experience and manage the emotional and mental health challenges associated with the transition to university life. Thematic analysis revealed four key themes: i) declining mental health marked by heightened anxiety and depression; ii) fluctuating self-esteem due to academic pressures and newfound independence; iii) financial stress exacerbating emotional distress; and iv) the role of therapy and professional help in managing mental health concerns. The findings contribute to the growing discourse on student mental health by offering insights into the psychological and emotional dimensions of university transition. The study provides important implications for policy and institutional practice, underscoring the need for comprehensive, student-centered support systems such as structured mental health programs, peer mentoring, and financial literacy workshops. Addressing these factors can enhance students’ well-being, academic performance, and retention. Despite its rich qualitative insights, the small sample size and self-reported data highlight the need for future mixed-method and longitudinal research.